Gaboxadol in Fragile X Syndrome: A 12-Week Randomized, Double-Blind, Parallel-Group, Phase 2a Study - Budimirovic, Dejan B.; Dominick, Kelli C.; Gabis, Lidia V.; Adams, Maxwell; Adera, Mathews; Huang, Linda; Ventola, Pamela; Tartaglia, Nicole R.; Berry-Kravis, Elizabeth (Frontiers in Pharmacology, 2021)
Background: Fragile X syndrome (FXS), the most common single-gene cause of inherited intellectual disability and autism spectrum disorder (ASD), is caused by a full-mutation expansion of the fragile X mental retardation 1 (FMR1) gene. Individuals with FXS present with a wide range of neurobehavioral impairments such as cognitive, language, and adaptive deficits; ASD; anxiety; social withdrawal and avoidance; and aggression. Decreased expression of the γ-aminobutyric acid type A (GABAA) receptor δ subunit and deficient GABAergic tonic inhibition could be associated with those symptoms. Gaboxadol (OV101) is a δ-subunit–selective, extrasynaptic GABAA receptor agonist that enhances GABAergic tonic inhibition, providing the rationale for study of OV101 as a potential targeted treatment of FXS. No drug is approved in the US for the treatment of FXS. Methods: This 12-week, randomized (1:1:1), double-blind, parallel-group, phase 2a study was designed to assess the safety, tolerability, efficacy, and optimal daily dose of OV101 5 mg (once [QD], twice [BID], or three-times daily [TID]) in adolescent and adult males with FXS. Safety as the primary study objective assessed for treatment-emergent (TEAEs) and treatment-related ones leading to study discontinuation, and serious adverse events (SAEs). The secondary study objective assessed for the effect of OV101 on a variety of problem behaviors. Results: A total of 23 participants with FXS (13 adolescents, 10 adults) with moderate-to-severe neurobehavioral phenotypes (Full Scale Intelligence Quotient, 41.5 ± 3.29; ASD, 82.6%) were randomized to the 5 mg (n = 8), 10 mg (n = 8), or 15 mg (n = 7) for 12 weeks. OV101 was well tolerated across all 3 dosages. The most common TEAEs were upper respiratory infection (n = 4), headache (n = 3), diarrhea (n = 2), and irritability (n = 2). No SAEs were reported. Improvements from baseline to end-of-treatment were observed on several efficacy endpoints, and 60% of participants were treatment responders based on Clinical Global Impressions-Improvement. Conclusions: Overall, OV101 was safe and well tolerated. Efficacy results from this first interventional clinical study of gaboxadol in FXS suggest that OV101 has potential therapeutic benefit in adolescent and adult males with this disorder.